Predictors of Significant Liver Fibrosis in People with Chronic Hepatitis C Who Inject Drugs in the Czech Republic - Frankova, Sona; Uzlova, Nikola; Merta, Dusan; Pitova, Veronika; Sperl, Jan (Life (Basel, Switzerland), 2023)
BACKGROUND AND OBJECTIVES: HCV infection often remains untreated in people who inject drugs (PWID), albeit they may present with advanced liver fibrosis at a young age. We aimed to assess the rate of patients with significant fibrosis in PWID starting anti-HCV therapy and identify the factors associated with severe fibrosis. METHODS: The cohort of 200 patients was divided into two groups: F0-F2 (N = 154, 77%), patients with liver stiffness measurement (LSM) < 10.0 kPa, and F3-F4 (N = 46, 23%), with LSM ≥ 10.0 kPa, indicating significant liver fibrosis. RESULTS: In group F3-F4, there were significantly more males, and the patients were older, with a higher BMI. The number of long-term abstaining patients was significantly higher in group F3-F4 compared with group F0-F2, as well as the proportion of patients reporting harmful drinking. Obesity (OR 4.77), long-term abstinence from illicit drugs (OR 4.06), harmful drinking (OR 2.83), and older age (OR 1.17) were significant predictors of advanced fibrosis in PWID starting anti-HCV therapy. CONCLUSIONS: A quarter of PWID presented with significant liver fibrosis at treatment initiation. Obesity, long-term drug abstinence, harmful drinking, and older age contributed to significant liver fibrosis.
Keywords: significant liver fibrosis; harmful drinking; obesity; age; people who inject drugs; chronic hepatitis C